A step forward in health-related IoT cybersecurity: remarks on the proposal for a liability for defective products directive - Greser, Jarosław (Frontiers in Digital Health, 2023)
This article outlines the efforts of the European Union in health-related IoT (H-IoT) cybersecurity. The first part identifies cyber threats that are specific to H-IoT. The second part covers the overall regulatory picture and briefly addresses both existing law and legislative initiatives. The third part discusses the Proposal for a Liability for Defective Products Directive and the measures it contains that relate directly to H-IoT.